Tautomerism and bioactivities of curcumenol, a common sesquiterpenoid widely existing in edible plants. Issue 3 (7th March 2019) - Zhang, Li-Sha; Shen, Sheng-Nan; Gao, Yu-Li; Shi, Shui-Yang; Zhou, Chang-Xin; Mo, Jian-Xia; Xu, You-Kai; Lin, Li-Gen; Gan, Li-She
Abstract : Curcumenol was discovered as hemiacetal–ketone tautomers with enhanced antioxidative activity and it markedly promoted myogenic differentiation and mitochondrial function. Abstract : Curcumenol was firstly revealed as a pair of hemiacetal–ketone tautomers in solutions by using temperature variation 1 H-NMR experiments, 2D NMR, and chemical methods. Quantum chemical calculation allowed the explanation of its spectroscopic behavior. An antioxidative SAR study on its derivatives verified the tautomeric bio-significance. Curcumenol also remarkably enhanced myogenic differentiation and mitochondrial function.